2023
DOI: 10.1021/acsami.2c17958
|View full text |Cite
|
Sign up to set email alerts
|

Study of a High-Voltage NMC Interphase in the Presence of a Thiophene Additive Realized by Operando SHINERS

Abstract: Improving the electrochemical properties and cycle life of high-voltage cathodes in lithium-ion batteries requires a deep understanding of the structural properties and failure mechanisms at the cathode electrolyte interphase (CEI). We present a study implementing an advanced Raman spectroscopy technique to specifically address the compositional features of interphase during cell operation. Our operando technique, shell-isolated nanoparticle-enhanced Raman spectroscopy (SHINERS), provides a reliable platform t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…ΔV A is a tool to estimate the internal resistance of LIB cells. [ 29,39 ] As shown in Figure 1b, both cells containing the considered electrolyte formulations showed a continuous increase in resistance with ongoing galvanostatic cycling. However, it was observed that the resistance of the cells containing the baseline electrolyte increased significantly faster with ongoing galvanostatic cycling, reaching a ΔV of 850 mV after 500 cycles.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…ΔV A is a tool to estimate the internal resistance of LIB cells. [ 29,39 ] As shown in Figure 1b, both cells containing the considered electrolyte formulations showed a continuous increase in resistance with ongoing galvanostatic cycling. However, it was observed that the resistance of the cells containing the baseline electrolyte increased significantly faster with ongoing galvanostatic cycling, reaching a ΔV of 850 mV after 500 cycles.…”
Section: Resultsmentioning
confidence: 93%
“…The first one (A) is similar to the polymerization mechanism of thiophene, which was considered in our previous work, where the oxidized additive is deprotonated by a PF 6 − anion. [ 29 ] Additionally, a second mechanism (B), where the proton is intramolecularly transferred to the semi‐deprotonated boronic acid group instead of the deprotonation via an external anion, was suggested. Please note that the calculated energies of the reaction mechanisms in Figure 3 in electron volts (eVs) are equivalent to potentials in volts, as only one electron is transferred per elementary reaction step.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations